2021
DOI: 10.1039/d1gc00648g
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable, reprocessable, self-adhered and repairable carbon fiber reinforced polymers using full biobased matrices from camphoric acid and epoxidized soybean oil

Abstract: Carbon fiber reinforced epoxy is the most commonly used carbon fiber composite with superior performance. However, the growing demand of carbon fibers reinforced epoxy results in a huge consumption of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 63 publications
1
49
0
Order By: Relevance
“…The matrix of common CFRCs is usually a permanent cross-linked resin, leading to difficult recovery of CFs and poor reprocessability of CFRCs. , TOTGE–MDA 1.0 was selected as a CFRC matrix due to its high DTER rate, which facilitates reprocessing and rapid degradation of CFRCs. Furthermore, the TOTGE–MDA 1.0 vitrimer matrix exhibits superior mechanical and thermal properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The matrix of common CFRCs is usually a permanent cross-linked resin, leading to difficult recovery of CFs and poor reprocessability of CFRCs. , TOTGE–MDA 1.0 was selected as a CFRC matrix due to its high DTER rate, which facilitates reprocessing and rapid degradation of CFRCs. Furthermore, the TOTGE–MDA 1.0 vitrimer matrix exhibits superior mechanical and thermal properties.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they have promising applications in the field of CFRCs. In particular, owing to their superior mechanical properties and high chemical resistance, vitrimers based on a dynamic transesterification reaction (DTER) can be excellent candidates as matrices for CFRCs. Ma et al obtained fully bio-based thermosets by curing epoxidized sucrose soyate with citric, malic, and tartaric acids. These thermosets can be degraded by aqueous sodium hydroxide solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, various groups of researchers have tried to obtain composites from recyclable eco-materials. For example, Zhang et al [90] manufactured CF composites using biobased dynamic crosslinked matrices from natural epoxidized soybean oil and camphoric acid, without additional chemical modification. The authors observed that the newly developed composites highlight a usable performance at 25 • C. In addition, their laminates can be easily repaired and reprocessed at high temperatures.…”
Section: Advantages and Limitations Of Frp Manufacturing Methodologiesmentioning
confidence: 99%
“…Natural polymers such as lignin have distinct chemical structures and unique properties that make them attractive and potentially sustainable components of vitrimers. Following this trend, last years have experienced coherent development of biobased vitrimers, owing to the lucrative properties of vitrimers and the relatively high abundance and low cost of the raw materials. , However, in most cases, chemical modification of the bio-based starting materials is needed to generate synthons able to react and form dynamic covalent networks, in addition to the use of catalysts to trigger the reversibility of dynamic covalent bonds. ,, This pre-processing or fractionation of natural polymers, together with the need of catalysts, hinders their scalability toward industrial processes and therefore limits their potential applications. This present scenario poses an important challenge to avoid the chemical or physical pre-modification and functionalization of renewable raw materials that are available in a sufficient scale and at a low cost for industrial end uses.…”
Section: Introductionmentioning
confidence: 99%